Large‐area single‐photon‐counting CdTe detector for synchrotron radiation computed tomography: a dedicated pre‐processing procedure. (12th June 2018) - Brombal, Luca; Donato, Sandro; Brun, Francesco; Delogu, Pasquale; Fanti, Viviana; Oliva, Piernicola; Rigon, Luigi; Di Trapani, Vittorio; Longo, Renata; Golosio, Bruno
Abstract : Large‐area single‐photon‐counting CdTe detectors are attractive due to their high‐efficiency, low‐noise and spectral performances but they still present several non‐optimal behaviours ( e.g. charge trapping, inter‐module gaps etc. ). These issues are addressed in this article where a comprehensive step‐by‐step description of a pre‐processing procedure is presented and tested in the framework of a synchrotron radiation low‐dose tomographic application on breast specimens. Abstract : Large‐area CdTe single‐photon‐counting detectors are becoming more and more attractive in view of low‐dose imaging applications due to their high efficiency, low intrinsic noise and absence of a scintillating screen which affects spatial resolution. At present, however, since the dimensions of a single sensor are small (typically a few cm 2 ), multi‐module architectures are needed to obtain a large field of view. This requires coping with inter‐module gaps and with close‐to‐edge pixels, which generally show a non‐optimal behavior. Moreover, high‐ Z detectors often show gain variations in time due to charge trapping: this effect is detrimental especially in computed tomography (CT) applications where a single tomographic image requires hundreds of projections continuously acquired in several seconds. This work has been carried out at the SYRMEP beamline of the Elettra synchrotron radiation facility (Trieste, Italy), in the framework of the SYRMA‐3D project, which aims to perform the world's first breast‐CT clinical study with synchrotron radiation. An ad hoc data pre‐processing procedure has been developed for the PIXIRAD‐8 CdTe single‐photon‐counting detector, comprising an array of eight 30.7 mm × 24.8 mm modules tiling a 246 mm × 25 mm sensitive area, which covers the full synchrotron radiation beam. The procedure consists of five building blocks, namely dynamic flat‐fielding, gap seaming, dynamic ring removal, projection despeckling and around‐gap equalization. Each block is discussed and compared, when existing, with conventional approaches. The effectiveness of the pre‐processing is demonstrated for phase‐contrast CT images of a human breast specimen. The dynamic nature of the proposed procedure, which provides corrections dependent upon the projection index, allows the effective removal of time‐dependent artifacts, preserving the main image features including phase effects.